Diet and physical activity modification: impact on adaptive behavior and biochemical measures of children with Down syndrome. - Kilany, Ayman; Elhadidy, Mohamed E.; Ganem, Mona M. F.; Nashaat, Neveen Hassan; Orabi, Ghada; Sakr, Mohamed A. (International Journal of Developmental Disabilities, 2024)
Objectives: Obesity in children with Down syndrome (DS) has negative implications for behavior. The aim was to assess the influence of weight reduction by diet modification with and without physical therapy sessions on adaptive behavior and some biochemical measures in children with DS with obesity. Methods: The study included 100 children with DS (56 males, 44 females; age range: 6–9 (8.5 ± 1.7) years. They were subjected to history taking, clinical examination, and the Vineland adaptive behavior scale. They were randomly divided into two groups: Group I underwent nutritional modification, and Group II was subjected to an added exercise program. The biochemical measures were estimated using the automated chemistry analyzer for blood chemistry (lipids), or ELISA. Results: An elevation of behavioral adaptive scores was noticed after the weight reduction, together with a reduction in the levels of triglycerides and an elevation of high-density lipoprotein-C levels. Levels of interleukin I, interleukin 6, and leptin were reduced in both groups. However, the improvement regarding the estimated measures was greater in Group II (p < 0.05). Conclusions: Weight reduction in children with DS was beneficial for their adaptive behavior and for adjusting dyslipidemia, along with some measures of inflammation. Combining physical activity with nutritional modification would help in the better advancement of the health and adaptive behavior of children with DS associated with obesity compared with isolated nutritional modification.